Producer income instability and farmers' risk response: The case of major Kenyan export crops - Klaus-Otto Junginger-Dittel; Thomas Mayer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1980)
The instability of export earnings in LDCs and its presumably harmful economic effects have been broadly discussed in the economic literature and among policy makers in international meetings. In analyzing these effects, the destabilization of producer incomes and farmers' risk response play a prominent role. Producer incomes may be destabilized by either domestic factors on the supply side (yield instability due to weather, crop diseases, etc.), or by fluctuating producer prices reflecting the instability of international primary commodity markets. If unstable producer incomes induce risk aversion among farmers, the sectoral factor input will be reduced and will be suboptimal from a welfare point of view, thus possibly hampering economic growth. The purpose of this paper is to quantify the effects of producer income instability on farmers' planting and long-run supply decisions in the coffee, tea, and sisal production of the Kenyan large farm sector. Coffee, tea, and sisal are the leading Kenyan export crops, the domestic consumption of which is negligible. About half of the Kenyan coffee and tea, and all the sisal are grown in the large farm sector, and nearly always on plantations. Coffee, tea, and sisal are permanent crops the planting of which requires long-run decisions. It is the long-run we shall focus on in this paper; hence the influence of income instability on short-term production planning will be neglected. The analysis will be based on a time series approach covering the period 1951-1975. In the following section we shall develop the methodological framework of how to measure the risk response of farmers. Next the estimation equations will be specified, and the estimation techniques will be demonstrated. Subsequently, the regression results are presented and interpreted. Some tentative conclusions are drawn in the final section.
Keywords: 330